Information and communication technology. The case of Italy - Ben Thabetova, Elisabeth; Frömmel, Tomáš; Máslo, Lukáš Augustin, 1985-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2017)
The aim of this research is to point out the main features of Information and Communication Technology, its spread in Italy at the beginning of the current century and the effect and performance ICT investments have within the economy. The theoretical part focuses on the reasons behind the importance of ICT studies and the roots of field researches. The practical part underlines Italys late in comparison to rest of the European countries and formulates a hypothesis based on the researches made in 2002 by Bresnahan, Brynjolfsson and Hitt around organizational changes within firms. The results of the research suggest that there is a significant interaction between investments in ICT and organizational changes and that these variables are complementary. Output is positively affected by implementation of ICT together with organizational changes; however, when occurring alone, ICT investments and organizational changes have low and negative impact on output. This result is significant to solve the problems of the low performance of ICT in the country, as it suggests firms would profit the most from a modern technological reorganization of management structures and business processes and, therefore, implementation in such direction should be made.
Vedoucí práce: Tomáš Frömmel
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses